Does the level of evidence underpinning nice recommendations influence adoption into trust maternity guidelines?. (7th June 2011) - Kidney, E; Jolly, K; Kenyon, S
Abstract : Introduction: Maternity care providers are expected to follow National Institute for Health and Clinical Excellence (NICE) and other evidence-based guidelines.1 Aims: To audit whether level of evidence influences adoption of NICE guidelines by Trusts and explore factors influencing implementation. Methods: Structured audit of maternity guidelines from 12 out of 15 Trusts in the West Midlands, England, for incorporation of 15 NICE recommendations, 2 – 5 selected on basis of evidence level and CNST6 requirement. Semi-structured interviews with 16 clinicians from five Trusts explored implementation into practice of recommendations on delay in first stage of labour and perineal care. Results: Full adoption into local guidelines ranged from 100% for skin-to-skin contact and suture materials to 55% incorporating the 2-h wait for suspected delay in labour and 25% stipulating breastfeeding within the first hour. Trust policy influenced NICE implementation, with presumption of adoption of guidance an important facilitator. Interactions between obstetricians and midwives influenced both adoption and implementation of recommendations on suspected delay. Inclusion in guidelines, training, support, audit and feedback increased confidence. Widespread dissemination and training meant NICE perineal care recommendations were strongly believed to be beneficial, re-enforced by better detection of third degree tears. Barriers were lack of confidence and a previous culture of passing responsibility for repair to medical staff. Conclusion: The robustness of evidence underpinning recommendations was not an important factor in adoption of guidance and Trust boards should adopt NICE guidelines unless there is evidence for not doing so. Changes in practice that cross professional boundaries may require additional support.